Structural challenges in design and detailing of skybridges connecting tall buildings - Kiriparan, B.; Waduge, B.; Fernando, W.J.B.S.; Mendis, P. (10th International Conference on Structural Engineering and Construction Management (ICSECM), 2019)
Implementation of skybridges between towers is becoming trendy these days in the urbanizing world to achieve smart mobility in addition to the aesthetic, spatial and technical concerns. Emerging new technologies and thoughts of architects made the bridge to build at the higher elevation which challenging the structural engineers. Predicting the dynamic behaviour of the skybridge under wind, earthquake and other lateral loadings are vital. Selection of structural system for the bridge, connection configuration, any damping solution if required are comprehensively discussed in this paper through a case study. The detailed methodology for design and detailing of a skybridge that connecting fifty storied twin towers is well formulated in this paper considering all the aspects that studied through the literature survey. A finite element model is utilized to perform the analysis for the linked tall buildings under lateral loadings most importantly under wind loadings. The roller connection is achieved by the customized guided slide bearings. Further, the viscous dampers are proposed as a supplementary solution to mitigate the excessive relative movements thus the human comfort is preserved. The authors have also addressed the aerodynamic stability of the skybridge in this study.
Keywords: Skybridges; Structural coupling; Bearings; Viscous damper; Aerodynamic stability